HUBUNGAN KECERDASAN EMOSIONAL DAN MINAT BELAJAR DENGAN PRESTASI BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 16 MEDAN - Syamsu Nahar; Wahyudin Nur Nasution; DTM Ayub Azhari (Edukasi Islami : Jurnal Pendidikan Islam, 2020)
This study uses a quantitative approach. The variables of this study consisted of the dependent variable and the independent variable. The purpose of this study was to determine the magnitude of the relationship between the dependent variable (dependent variable) and the independent variable (Independent variable). This research method is classified as correlational research. The population consisted of all students of Medan 16 Public High School, totaling 900 students in 2020. The study sample was determined to be 100 students and the sampling was done by means of Slovin with the formula n = N / (1 + N (e)2). Data collection tools using a questionnaire in the form of a Likert scale and also the pree test and post test. The research instruments were arranged according to variable indicators based on the direction and guidance of the Thesis advisor, then tested on students of Medan 16 High School. It is known that all X1 variable instruments consisting of 40 items from X2 variables consisting of 40 items. Test requirements for data analysis of variables X1, X2 and Y using the test for normality, homogeneity and linearity. Hypothesis testing uses the t test to look for correlations on each variable and the partial correlation test uses the product moment formula or SPSS version 20. The results of the research hypothesis which reads that there is a positive and significant relationship between emotional intelligence and interest in learning with learning achievement in Islamic Religious Education subjects, with proven that r arithmetic> rtable and also rithmetic> ttable that can be accepted at a significance level of 0.05.